Experience of stigma in private life of relatives of people diagnosed with schizophrenia in the Republic of Belarus - Krupchanka, D; Kruk, N; Murray, J; Davey, S; Bezborodovs, N; Winkler, P; Bukelskis, L; Sartorius, N (Social psychiatry and psychiatric epidemiology, 2016)
PURPOSE: Family stigma constitutes a major problem in schizophrenia worldwide. Data on first-hand experience of stigma in families is necessary for planning and implementing interventions to reduce its burden. The aim of the study was to investigate the experience of stigma among relatives of persons with schizophrenia in Belarus. METHODS: Qualitative research methods, such as the thematic analysis of in-depth semi-structured interviews with 20 relatives of people diagnosed with schizophrenia, were used. Experience of discrimination, strategies used to cope with it, and requests for interventions were investigated. RESULTS: The most salient themes in experience of stigma in the private domain of life elicited in the narratives included anticipated stigma and dissolution of families. The experience of stigma was associated with burdensome feelings of guilt, tiredness and loneliness, together with fear and anxiety due to uncertainty in the future and sorrow because of frustrated hopes in past. Analysis of the strategies used to overcome the difficulties revealed concealment and "life behind closed doors", avoidance of the rest of the family, taking full responsibility and sacrificing one's personal life. CONCLUSION: To reduce the burden of stigma in the private life of the family members of people living with schizophrenia in Belarus, important steps should be taken to promote the empowerment of families including: reforming mental health services; provision of better access to information; family support services, community care; development of family organisations; assistance in communication, re-socialisation and independent living for people diagnosed with schizophrenia.
Keywords: dospělí; Qualitative Research; Social Isolation; Female; Prejudice; Social Stigma; osoby pečující o pacienty; Adaptation, Psychological; Adult; ženské pohlaví; Schizophrenic Psychology; Běloruská republika; Republic of Belarus; lidé; Cost of Illness; sociální izolace; Caregivers; společenské stigma; schizofrenie; Courtesy stigma; adaptace psychologická; Family studies; Male; Qualitative approach; Schizophrenia; Developing Countries; rozvojové země; lidé středního věku; předsudek; mužské pohlaví; schizofrenie (psychologie); Middle Aged; osobní újma zaviněná nemocí; kvalitativní výzkum; Humans